Concurrent chemoradiotherapy with low dose weekly gemcitabine in medically inoperable muscle-invasive bladder cancer patients - ATASOY, BESTE MELEK; DANE, FAYSAL; ALSAN ÇETİN, İLKNUR (SPRINGER-VERLAG ITALIA SRL, 2014)
We aimed to determine the efficacy and the toxicity of low dose weekly gemcitabine with radiation therapy in medically unfit muscle-invasive bladder cancer patients. Twenty-six patients were included into the retrospective analysis. Weekly gemcitabine was administered 75 mg/m(2) with a median dose of 63 Gy radiation therapy. Clinical target volume was defined as the urinary bladder only in conformal treatment planning. Median follow-up was 51 months (range 14-118 months). Complete response rate was 62.5 %. The 5-year local progression-free survival, disease-specific survival and overall survival rates were 40.6, 59.5 and 58.5 %, respectively. Concurrent chemotherapy was continued in 80.7 % of patients without any interruption. Gemcitabine was stopped due to grade 3 thrombocytopenia (n = 1), cardiac angina (n = 1), chronic obstructive pulmonary disease exacerbation (n = 1) or patients' reluctance (n = 2). Low dose weekly gemcitabine with concurrent radiotherapy is a tolerable regimen and have comparable outcomes with platinum-based combined treatments in muscle-invasive bladder cancer. Prospective randomized trials can help in understanding the safety and efficacy of this treatment specially in medically unfit patients.
Keywords: Bladder cancer; Concurrent gemcitabine; Medically unfit patients; Radiotherapy; COMBINED-MODALITY PROGRAM; RADIATION-THERAPY; PHASE-I; NEOADJUVANT CHEMOTHERAPY; ORGAN PRESERVATION; RADIOTHERAPY; TRIAL; CISPLATIN